Perception of Islamic Religious Education Teachers Based on TPACK - Dahlia El Hiyaroh; Ifa Dotus Salimah; Muhammad Thohir (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2022)
This article analyzes the TPACK-based Islamic Religious Education Teacher's Perception at SMK Negeri Rengel-Tuban. This article uses descriptive qualitative research methods. Data were collected using observation, interviews, and surveys through the google form application. This study's participants comprised six people with details one female teacher and five male teachers. The results of this analysis indicate that PAI teachers at Rengel State Vocational School have a good perception of the use of the TPACK (technological pedagogical content knowledge) model and have a vital role in the field of Islamic Religious Education, namely, by mastering TPACK, PAI teachers can present innovative learning. And creative and effective in the classroom, implementing online learning through TPACK has succeeded in increasing teacher competencies such as online classroom management competencies.